ANALISIS PENGGUNAAN PROBLEM BASED LEARNING DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS DAN KEAKTIFAN SISWA MATA PELAJARAN BIOLOGI - Widya Ayu Paramitha; Eny Hartadiyati Wasikin Haryanti; Tri Hastutiningsih (Pascasarjana Universitas PGRI Semarang, 2024)
This research aims to increase students' activeness and critical thinking abilities in biology subjects through the application of the Problem Based Learning learning model. The background is that students are very passive when learning activities take place and their skills in asking and answering questions are still limited to memory and understanding. This type of research is Classroom Action Research (PTK) which is carried out in three cycles. The data collection techniques used are test and non-test techniques. Data analysis techniques use descriptive and quantitative analysis. The research subjects were 31 students consisting of 12 male students and 19 female students. The research results showed an increase in students' activeness and critical thinking. The percentage of active students increased in cycle I to 51.7%, then increased in cycle II to 55.7% and increased in cycle III to 59.5% of active students. Increased critical thinking skills can also be seen through PBL learning with pre-test and post-test scores increasing in each cycle. In cycle I the average pre test score was 36.4, then it increased in cycle II to 45.1, and in cycle III it was 59.6, the pre test of the three cycles was still below the KKM. The average post test score in cycle I was 60.6, then increased in cycle II to 75.4, and in cycle III 84.1, post test in cycle I was still below the KKM, while in cycles II and III it had exceeded the KKM.